EFFECT OF PROPOLIS AND N-ACETYLCYSTEINE SUPPLEMENTATION ON LIPOPROTEIN SUBCLASSES DISTRIBUTION AND PARAOXONASE 1 ACTIVITY IN SUBJECTS WITH ACUTE RESPIRATORY INFECTION - Vekić, Jelena; Ivanišević, Jasmina; Zeljković, Aleksandra; Spasojević-Kalimanovska, Vesna; Bogavac-Stanojević, Nataša; Mihajlović, Marija; Janać, Jelena; Vujčić, Sanja; Miljković, Milica; Žujović, Dejan; Kotur-Stevuljević, Jelena (Journal of Medical Biochemistry, 2020)
Background: Propolis and N-acetylcysteine have positive impact on respiratory tract health. Also, it has been suggested that they have beneficial effects on serum lipid and oxidative stress status, but the available data are limited and mostly gained from animal models. In this study we evaluated the effects of propolis and N-acetylcysteine supplementation (PropoMucil®) on lipid status, lipoprotein subclasses distribution and paraoxonase 1 activity in subjects with acute respiratory infection.Methods: Twenty subjects with acute respiratory infection were included. PropoMucil® granules for oral solution (80 mg of dry propolis extract and 200 mg of N-acetylcysteine) were administered tree times per day for ten days. Serum lipid profile, paraoxonase 1 activity and low-density and high-density lipoprotein size and subclasses distribution were assessed at baseline and after supplementation.Results: Following ten days of supplementation lipid status remained unchanged, but a significant increase of lowdensity lipoprotein particle size and proportion of high-density lipoprotein 3a particles were found (P